Deep learning speech recognition for residential assistant robot - Robinson Jiménez-Moreno; Ricardo A. Castillo (Institute of Advanced Engineering and Science, 2023)
This work presents the design and validation of a voice assistant to command robotic tasks in a residential environment, as a support for people who require isolation or support due to body motor problems. The preprocessing of a database of 3600 audios of 8 different categories of words like “paper”, “glass” or “robot”, that allow to conform commands such as